Research on the Sustainable Development of Urban Night Tourism Economy: A Case Study of Shenzhen City - Zhang, Rui; Chen, Sirong; Xu, Shaogui; Law, Rob; Zhang, Mu (Frontiers in Sustainable Cities, 2022)
As the process of cultural tourism integration gradually deepens, determining how to tap into the night tourism economy has become a new focus of the industry. Among the core cities in the Guangdong-Hong Kong-Macao Greater Bay Area, Hong Kong and Macau have formed a more mature model of sustainable development of night tourism economy, whereas it is not obvious in mainland cities. The current research themes in this field are more scattered and have not yet formed a study with depth and breadth. Accordingly, this study selects the modern international metropolis Shenzhen as the research object. First, on the basis of system theory and sustainable development theory, it uses hierarchical analysis and comprehensive evaluation model to conduct a comprehensive assessment of the sustainable development of the tourism economy in Shenzhen from 2011 to 2021. Second, through the cluster analysis of day-time and night-time tourism economic patterns in Shenzhen, it explores the sustainable development path of Shenzhen's night-time tourism economy. Research results show that each major indicator of sustainable development of tourism economy in Shenzhen maintains a stable and fast growth momentum, and the rise of night-time tourism economy injects a new momentum for sustainable development. As an extension and supplement of the day-time tourism economic form, the night-time tourism economy includes three tourism economic forms: excursionistic, cultural immersion, and host and guest leisure. Finally, the researcher proposes corresponding sustainable development strategies for different forms of the night-time tourism economy. Empirical findings of this study have important reference value for the related research on night tourism economy.